Artem Medicalis – My ouroboros journey in art and science (Journal of EAHIL, 2019)
Artistic scientific research is, I believe, one of the ways out of the cul-de-sac that modern art brought us into during the latter part of the twentieth century. By returning to serious scientific and anatomical study, doors opened to a new discipline altogether. My personal journey as a medical artist took me from scientific wonder and intense interest in alchemy, through artistic anatomical research, on to functional medical illustration and back to conceptual art and sculpture. Having completed a course in forensic facial reconstruction I developed the idea of making a reconstruction of Andreas Vesalius’s face. Thus, began a quest to find the lost grave of the great anatomist. We have not found it yet but have already changed history.